Causes of Internal Migration and Its Impact on Poverty: A Case Study from Kurigram District in Bangladesh (Applied Research and Innovation, 2024)
Internal migration plays a pivotal role in poverty reduction, and this phenomenon is widespread in Bangladesh. While some studies based on secondary data have been published on internal migration, the definitive conclusions drawn from this data remain unclear. Therefore, to address this gap, our study fills the void by utilizing primary data. The research primarily relies on data collected through interviews, encompassing 300 respondents who migrated, 100 family members of migrants, and 82 individuals from their kinship networks. The study uncovers crucial findings regarding the causes of internal migration and its impact on poverty. Furthermore, it sheds light on the theoretical underpinnings of migration theory. One significant discovery of the study is that the living standards of respondents improve after migration compared to their pre-migration living conditions. Additionally, this paper delves into the examination of socioeconomic and socio-demographic factors that influence the decision-making process of internal migration. By employing primary data and conducting in-depth analyses, this research provides a more comprehensive understanding of the intricacies surrounding internal migration and its effects on poverty alleviation.